Character evolution and the origin of Caimaninae (Crocodylia) in the New World Tropics: new evidence from the Miocene of Panama and Venezuela. (16th June 2016) - Hastings, Alexander K.; Reisser, Moritz; Scheyer, Torsten M.
Abstract: Alligators and caimans share a close relationship, supported by both molecular and morphological characters. The divergence between alligators and caimans has been difficult to discern in the fossil record. Two basal taxa have recently been described from the Miocene of Panama and Venezuela but have not yet been presented in a joint phylogeny. Continued preparation of the type material of the Venezuelan Globidentosuchus brachyrostris Scheyer et al., 2013 has revealed new characters for scoring in a cladistic framework. In addition, the first lower jaw of the Panamanian Centenariosuchus gilmorei Hastings et al., 2013 is described herein, and additional characters were scored. In total, we conducted five cladistic analyses to better understand the character evolution involved in the establishment of Caimaninae. In each case, Globidentosuchus appears as the basal-most of the caimanine lineage, followed by Culebrasuchus mesoamericanus Hastings et al., 2013 from Panama. Stepwise character additions of synapomorphies define progressively more derived caimanines, but stratigraphic context creates ghost lineages extending from the Miocene to Paleocene. The persistence of two basal taxa into the Miocene of northern South America and Central America supports the concept of a relict basal population in this region. This further supports biogeographic hypotheses of dispersals in both directions between North and South America prior to full land connection.